THE EFFECT OF UNEMPLOYMENT LEVELS ON POVERTY LEVELS IN PALEMBANG CITY REGION - Idul Maldi; Novita Julianti; Anggun Citra Abadi; Maya Panorama (SEAN Institute, 2023)
Unemployment and poverty are two macroeconomic indicators. This research discusses the problem of the unemployment rate against the poverty rate in the city of Palembang in 2020–2021. The purpose of this study is to determine the effect of the unemployment rate in the city of Palembang on the poverty rate in 2020–2021. This study uses multiple linear analysis methods with secondary data and a quantitative approach. Unemployment or joblessness is a term given to people who do not work at all or who are looking for work. Unemployment can also be interpreted as a situation when someone does not have a job. Unemployment is also generally found in the number of workers or someone looking for work that is not proportional to the number of available jobs they can get. Therefore, problems in the economy due to unemployment can reduce productivity and income in society, which can lead to poverty and other social problems. Unemployment, according to BPS, is a resident who is not working but is looking for work or preparing for a business, or feels that it is impossible to get a job (is desperate), or has been accepted to work but has not started working yet. BPS determines the poverty criteria using the basic needs approach, while the poverty indicators used are the head count index and the severity index,